GAMBARAN PENANGANAN MANDIRI IBU HAMIL DENGAN EMESIS GRAVIDARUM PADA TRIMESTER I DI BKIA RUMAH SAKIT WILLIAM BOOTH SURABAYA - ., Intyaswati, Maria Martina (D3 Kebidanan, 2013)
Nausea and vomiting is one of the earliest symptoms, most common and most important as a cause of stress associated with pregnancy. Most of the pregnant woman will try to cope with symptoms of nausea and vomiting themselves how they feel. Habits of pregnant women who solve their own problems of nausea and vomiting, sometimes consciously or unconsciously, may endanger the health of mother and fetus. In fact, pregnant women will try to consume everything, which is expected to reduce nausea and vomiting. On this note, good nutrition is almost irrelevant to the treatment of nausea and vomiting. Based on these problems, researchers are conducting research on "self-image handling pregnant women with emesis gravidarum in the first trimester in BKIA William Booth Hospital Surabaya" in order to find out how the image of an independent treatment of pregnant women with emesis gravidarum in the first trimester, if the mother does the handling of self well or not. In this study researchers used a descriptive design, with a single variable and the study population was all pregnant women who visited BKIA William Booth Hospital Surabaya with a sample of 67 respondents and sampling techniques are consecutive sampling. Data collected from the charge sheet prepared by a descriptive questionnaire using the table of distributive confirmed as a percentage, then narrated. The study obtained data on maternal self-image handling with emesis gravidarum in the first trimester of the respondent who did well handling 8 people (12%), good enough 40 people (60%), less well 19 people (23%) and handling is not good no (0%). It is therefore expected health workers, especially in BKIA can improve quality of care by providing health care for all pregnant women who visit the BKIA, for mothers who have not been able to perform independently with good handling, or still less able to do well.Key words: self-treatment, emesis gravidarum